ESG Pillars and Bank Performance: Evidence from European Banks with a Focus on Nordea - Rahim, Dariush (My University, 2026)
Environmental, Social, and Governance are a crucial part of companies and are used to assess, a company’s sustainability, risk management, and long-term value. The legal obliga-tion to report on ESG is constantly increasing due to transparency. This study examines the relationship between ESG integration and banks’ financial performance, with a partic-ular focus on European Banks and Nordea as a benchmark. The goal of this study is to de-termine which ESG factors have the biggest effects on financial performance and to exam-ine if ESG pillars affect profitability, stock volatility, and cost of capital. The empirical analysis is based on panel data covering European banks from 1999 to 2024. The dataset includes financial variables such as Return on Equity (ROE), Return on Asset (ROA), stock price volatility, ESG scores and individual pillars, Environmental (E), Social (S) and Governance (G) Pillars. The study uses panel regression methods, including Fixed Ef-fects and Random Effects models, and the Hausman test is used to determine the most appropriate model specification. The results show that there is no consistent positive correlation between profitability and the Overall ESG score. The disaggregated study, on the other hand reveals that financial performance is positively and statistically significantly correlated with each of the ESG pillars, particularly Social (S) and Governance (G) pillars. Although the Environmental (E) pillar is not as strong, it has a favorable impact. These results suggest that significant varia-tions between ESG pillars may be hidden by the overall ESG score. The findings also suggest that the influence of ESG factors on stock price volatility and cost of capital is more restricted and inconsistent. This suggests that although ESG integration may have an impact on some areas of financial performance, not all financial measures are affected in the same way. The results also indicate that while ESG-related investments have short-term costs, their long-term advantages may become clear. Overall, the study contributes to the existing literature by proving how ESG integration affects banks’ financial performance in a variety of ways. The findings highlight the im-portance of examining ESG pillars independently since different ESG pillars have different impacts on financial results. The findings are relevant for financial institutions, investors, and policymakers, as the findings highlights the role of Governance (G) and Social (S) fac-tors in driving the financial performance of the banking sector.

Ympäristö-, yhteiskunta-, ja hallintotapa-asiat (ESG) ovat yrityksille keskeinen osa-alue, ja niiden avulla arvioidaan muun muassa yrityksen kestävyyttä, riskienhallintaa ja pitkän aika-välin arvoa. Lainsäädännöllinen velvollisuus raportoida ESG-asioista kasvaa jatkuvasti. Tässä tutkimuksessa tarkastellaan ESG-tekijöiden integroinnin ja pankkien taloudellisten tulosten välistä suhdetta, keskittyen erityisesti eurooppalaisiin pankkeihin ja Nordeaan vertailukohteena. Tämän tutkimuksen tavoitteena on selvittää, mitkä ESG-tekijät vaikuttavat eniten taloudelliseen tulokseen, sekä tutkia, vaikuttavatko ESG-pilarit kannattavuuteen, osake-kurssien volatiliteettiin ja pääomakustanuksiin. Empiirinen analyysi perustuu paneeliaineistoon, joka kattaa eurooppalaiset pankit vuosilta 1999-2024. Aineisto sisältää taloudellisia muuttujia, kuten oman pääoman tuotto (ROE), kokonaispääoman tuoton (ROA), osakekurssien volatiliteetin, ESG-pisteeseen (ESG Score) sekä yksittäiset pilarit: Ympäristö (E), sosiaalinen (S) ja hallinto (G). Tutkimuksessa käytetään paneeliregressiomenetelmiä, mukaan lukien kiinteiden ja satunnaisten vaikutusten mallit, ja sopivimman mallin määrittämiseen käytetään Hausmanin testiä. Tulokset osoittavat, että ESG-kokonaispisteet (ESG scores) eivät ole johdonmukaisesti positiivisessa suhteessa kannattavuuteen. Sen sijaan erittelyanalyysi osoittaa, että yksittäisillä ESG-pilareilla, erityisesti sosiaalisella (S) ja hallintotavalla (G), on positiivinen ja tilastollisesti merkittävä yhteys taloudelliseen tulokseen. Myös ympäristöpilarilla (E) on positiivinen, mutta heikompi vaikutus. Nämä havainnot viittaavat siihen, että ESG-kokonaispisteet saattavat peittää tärkeitä eroja ESG-ulottuvuuksien välillä. Lisäksi tulokset osoittavat, että ESG-tekijöillä on rajallisempi ja epäjohdonmukaisempi vaikutus osakekurssien volatiliteettiin ja pääomakustannuksiin. Tämä viittaa siihen, että vaikka ESG-integraatio saattaa vaikuttaa tiettyihin taloudellisen tuloksen osa-alueisiin, sen vaikutukset eivät ole yhtenäisiä kaikkien taloudellisten indikaattoreiden osalta. Tulokset korostavat myös, että ESG-sijoituksiin voi liittyä lyhyen aikavälin kustannuksia, kun taas niiden hyödyt saattavat toteutua pidemmällä aikavälillä. Kaiken kaikkiaan tutkimus täyttää olemassa olevaa kirjallisuutta tarjoamalla näyttöä siitä, että ESG-integraatiolla on moniulotteinen vaikutus pankkien taloudelliseen tulokseen. Tulokset korostavat ESG-pilareiden erillisen analysoinnin tärkeyttä, sillä eri ESG-pilarit voivat vaikuttaa taloudellisiin tuloksiin eri tavoin. Tulokset ovat erityisen merkityksellisiä rahoituslaitoksille, sijoittajille ja päätöksentekijöille, sillä he korostavat hallinnon ja sosiaalisten tekijöiden roolia pankkisektorin taloudellisen tuloksen ajurina.
Keywords: banking sector; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance; Rahoitus